2016
DOI: 10.1177/1087054713508602
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Readiness Potential in the Absence of Executive Dysfunction in Adults With ADHD

Abstract: In adults with ADHD, deficits of motor organization are also manifest in situations not involving external stimulus processing. The attenuated RP occurred in the absence of executive dysfunction. Results are consistent with partial independence between motor and executive dysfunction in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…At first glance this may appear counterintuitive, in that if higher EF predicts greater activation across people, and responding to novel contexts is more executively demanding, one might expect the more demanding condition to elicit greater activation across conditions. Nevertheless, this pattern is consistent with other research that has demonstrated reduced preparatory neural activity in conditions of high versus lower cognitive demand (Baker et al, 2011), as well as in clinical conditions associated with motor and/or executive dysfunction (Golob & Starr, 2000; Praamstra et al, 2003; Seo, Sartory, Kis, Scherbaum, & Müller, 2013). At the same time, literature on healthy aging has generally demonstrated the opposite pattern of results, with older adults often exhibiting larger MRCP amplitudes relative to younger individuals (Berchicci et al, 2012; Falkenstein, Yordanova, & Kolev, 2006; Yordanova, Kolev, Hohnsbein, & Falkenstein, 2004), possibly reflecting compensatory processes or dedifferentiation of previously independent substrates (Park & Reuter-Lorenz, 2009; Seidler et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…At first glance this may appear counterintuitive, in that if higher EF predicts greater activation across people, and responding to novel contexts is more executively demanding, one might expect the more demanding condition to elicit greater activation across conditions. Nevertheless, this pattern is consistent with other research that has demonstrated reduced preparatory neural activity in conditions of high versus lower cognitive demand (Baker et al, 2011), as well as in clinical conditions associated with motor and/or executive dysfunction (Golob & Starr, 2000; Praamstra et al, 2003; Seo, Sartory, Kis, Scherbaum, & Müller, 2013). At the same time, literature on healthy aging has generally demonstrated the opposite pattern of results, with older adults often exhibiting larger MRCP amplitudes relative to younger individuals (Berchicci et al, 2012; Falkenstein, Yordanova, & Kolev, 2006; Yordanova, Kolev, Hohnsbein, & Falkenstein, 2004), possibly reflecting compensatory processes or dedifferentiation of previously independent substrates (Park & Reuter-Lorenz, 2009; Seidler et al, 2010).…”
Section: Discussionsupporting
confidence: 92%